Presence of cerebrospinal fluid antibodies associated with autoimmune encephalitis of humans in dogs with neurologic disease - Stafford, Emma G.; Kortum, Amanda; Castel, Aude; Green, Lauren; Lau, Jeanie; Early, Peter J.; Muñana, Karen R.; Mariani, Christopher L.; Yoder, Jeffrey A.; Olby, Natasha J. (Journal of veterinary internal medicine, 2019)
Background Presumed autoimmune diseases affecting the central nervous system (CNS) of dogs are common. In people, antibodies against neuronal cell surface antigens that are associated with a wide variety of neurological syndromes have been identified. The presence of cerebrospinal fluid (CSF) autoantibodies that target neuronal cell surface proteins has not been reported in dogs with neurologic disorders. Objectives Autoantibodies to neuronal cell surface antigens can be found in the CSF of dogs with inflammatory CNS disease. Our aim was to determine whether 6 neuronal cell surface autoantibodies were present in the CSF of dogs diagnosed with inflammatory and noninflammatory CNS disease. Animals Client‐owned dogs with CNS disease and complete diagnostic evaluation including magnetic resonance imaging and CSF analysis were included. One healthy dog was included as a negative control. Methods Cerebrospinal fluid was tested for 6 antigenic targets with a commercially available indirect immunofluorescence assay test kit. Results There were 32 dogs with neurological disease, 19 diagnosed with inflammatory disease (encephalitis and meningitis), 10 with noninflammatory disease (neoplasia, intervertebral disk disease, degenerative myelopathy, and epilepsy), 2 with no diagnosis, and 1 with neoplasia and meningoencephalitis. Anti‐N‐methyl‐d‐aspartate receptor 1 (NMDAR1) antibodies were detected in 3 dogs (3/32; 9.38%). All 3 dogs responded to treatment of meningoencephalomyelitis of unknown etiology (MUE). Conclusions and Clinical Importance Further evaluation of the prevalence and clinical relevance of CSF and serum antibodies to neuronal cell surface antigens is warranted. Defining antigenic targets associated with encephalitis in dogs might allow diagnostic categorization of MUE antemortem.